Neutron reflectivity of an adsorbed water-soluble block copolymer: A surface transition to micelle-like aggregates at the air/water interface - An, S; Su, T; Thomas, R; Baines, F; Billingham, N; Armes, S; Penfold, J (1998)
We describe neutron reflectivity measurements on layers of poly(2-(dimethylamino)ethyl methacrylate-block-methyl methacrylate) copolymer (poly(DMAEMA-b-MMA)) (70 mol % DMAEMA, Mn = 10k) adsorbed at the air/water interface. Measurements of the partially deuterated copolymer on null reflecting water give the adsorption isotherm and show that there is a surface phase transition from a layer about 20 Å thick to one about 40 Å thick. The concentration of polymer at which the phase transition occurs is close to that at which micellar aggregation in the bulk solution also occurs. Using two other isotopic compositions, the structure of the layer above and below the phase transition has been determined. At low concentration, the two blocks of the copolymer are approximately uniformly distributed in the direction normal to the interface and the layer is partially immersed in water. At high concentrations, the adsorbed layer has a cross-sectional structure resembling that expected for a micelle with the majority of the more hydrophobic MMA residues forming the core. The outer layers, comprising predominantly DMAEMA residues, are not equivalent, being much more highly extended on the aqueous side of the interface.